A Positive Stigma for Child Labor? - Patrinos, Harry Anthony; Shafiq, M. Najeeb (World Bank, Washington, DC, 2012)
The authors introduce a simple empirical model that assumes a positive stigma (or norm) toward child labor that is common in some developing countries. They illustrate the positive stigma model using data from Guatemala. Controlling for several child and household-level characteristics, the analysis uses two instruments for measuring stigma: a child's indigenous background and the household head's childhood work experience.